2013
DOI: 10.1002/pad.1667
|View full text |Cite
|
Sign up to set email alerts
|

Trust or Control? Private Development Cooperation at the Crossroads

Abstract: SummaryDevelopment NGOs are increasingly adopting so-called managerial working methods. This paper explores the changing belief systems and practices of Northern development NGOs as well as the strains arising from this pressure. We draw upon a literature review and case studies of two Northern development NGOs and their Southern counterparts in Ghana, India and Nicaragua. Our findings show that managerialist ideas and practices clash with a number of values, views and goals that 'traditionally' have been wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 56 publications
0
27
0
2
Order By: Relevance
“…In this view, “CSOs mainly have a technical service delivery role in promoting development rather than a political one” (Kamstra, 2017, p. 4) and are viewed instrumentally: they are to complement rather than oppose the efforts of states and donors. With the managerialism approach, CSO–donor relations are short‐term, contractual and top‐down (Elbers et al, 2014 as discussed in Kamstra, 2017, p. 4).…”
Section: The Dialogue and Dissent Programmementioning
confidence: 99%
See 1 more Smart Citation
“…In this view, “CSOs mainly have a technical service delivery role in promoting development rather than a political one” (Kamstra, 2017, p. 4) and are viewed instrumentally: they are to complement rather than oppose the efforts of states and donors. With the managerialism approach, CSO–donor relations are short‐term, contractual and top‐down (Elbers et al, 2014 as discussed in Kamstra, 2017, p. 4).…”
Section: The Dialogue and Dissent Programmementioning
confidence: 99%
“…The role of CSOs, then, goes beyond service delivery, also “addressing the root causes of poverty by challenging the underlying mechanisms of social, economic and political exclusion” (Banks & Hulme, 2012; Banks et al, 2015, both as cited in Kamstra, 2017, p. 5). This implies that donors should “complement and strengthen the efforts of their local partners by providing financial, institutional and moral support” (Elbers et al, 2014 as cited in Kamstra, 2017, p. 6). Donors should engage in long‐term, open‐ended and flexible relationships with CSOs, based on equality and trust, and CSOs should be allowed space to develop and change their agendas autonomously (Kamstra, 2017, p. 6).…”
Section: The Dialogue and Dissent Programmementioning
confidence: 99%
“…NGO‐led women’s empowerment efforts, particularly in non‐Western contexts, have been widely discussed in literature, and it is claimed that NGOs have a significant role in such activities (Elbers et al, 2014). For this study, it is crucial to identify the position of NGOs, particularly those working with refugees, on the empowerment of women.…”
Section: Ngo Migration and The Empowerment Of Womenmentioning
confidence: 99%
“…This is in stark contrast to the way the term is used across much of the academic literature, where 'partnerships' in development cooperation generally imply "a joint commitment to longterm interaction, shared responsibility for achievement, reciprocal obligation, equality, mutuality and balance of power" (Fowler 2000, 3). Studies of partnerships in development cooperation have found a frequent gap between the rhetoric and reality of cross-sector partnerships, with many partnerships being defined by the bureaucratic demands of donor organisations rather than partnership principles (Ashman 2001;Elbers et al 2014;Ellersiek 2011;Fowler 2000;Lister 2000;Vincent and Byrne 2006). …”
Section: Shifting Paradigmsmentioning
confidence: 99%